Comparison of microwave ablation and parathyroidectomy for treating severe secondary hyperparathyroidism - Li, Shuiping; Qiu, Jincheng; Zhang, Xiaoguang; Wang, Fuzhen; Yang, Xianrong; Chen, Xiaoyan; Guo, Xiaofang; Li, Zuolin; Lin, Min; Li, Xiaolian; He, Jinghua; Lyu, Guorong; et al. (Frontiers in Endocrinology, 2025)
ObjectiveThis study compared the efficacy of microwave ablation (MWA) and parathyroidectomy (PTX) in the treatment of secondary hyperparathyroidism (SHPT) and evaluated the improvement of bone metabolic markers (BMMs) and bone mineral density (BMD).Materials and methodsEligible patients with SHPT treated between January 2019 and August 2022 were enrolled in the study and were divided into two groups: MWA and PTX. Outcome measures included the treatment success rate, percentage of patients whose intact parathyroid hormone (iPTH) concentration was within the target range, serum calcium (Ca), phosphorus (P), alkaline phosphatase (ALP), osteocalcin (OC), C-terminal cross-linked telopeptide of type I collagen (β-CXT), and BMD. Data on the procedure time, intraoperative blood loss volume, length and cost of hospitalization, incidence of postoperative complications, and recurrence rates were analyzed.ResultsA total of 107 patients with SHPT—48 in the MWA group and 59 in the PTX group— were included in the study. There were no significant differences in baseline data between the two groups (p>0.05). At the final follow-up, both therapies decreased iPTH, Ca, P, ALP, OC, and β-CXT levels and increased BMD (p<0.05). Nonetheless, the decrease in iPTH, ALP, OC, and β-CXT was more pronounced 6 and 12 months after PTX (p<0.05). The percentage of patients whose iPTH level was within the target range was significantly higher in the MWA group (p<0.05). The incidence of severe hypocalcemia was significantly lower in the MWA group (p<0.05).ConclusionMWA can improve BMMs and BMD, and is a minimally invasive approach with great potential for treating patients with SHPT who cannot tolerate PTX.